Prenatal enrichment and recovery from perinatal cortical damage: effects of maternal complex housing - Gibb, Robbin L.; Gonzalez, Claudia L. R.; Kolb, Bryan (Frontiers in Behavioral Neuroscience, 2014)
Birth is a particularly vulnerable time for acquiring brain injury. Unfortunately, very few treatments are available for those affected. Here we explore the effectiveness of prenatal intervention in an animal model of early brain damage. We used a complex housing paradigm as a form of prenatal enrichment. Six nulliparous dams and one male rat were placed in complex housing (condomom group) for 12 hours per day until the dams' delivered their pups. At parturition the dams were left in their home (standard) cages with their pups. Four dams were housed in standard cages (cagemom group) throughout pregnancy and with their pups until weaning. At postnatal day 3 (P3) infants of both groups received frontal cortex removals or sham surgery. Behavioural testing began on P60 and included the Morris water task and a skilled reaching task. Brains were processed for Golgi analyses. Complex housing of the mother had a significant effect on the behaviour of their pups. Control animals from the condomom group outperformed those of the cagemom group in the water task. Condomom animals with lesions performed better than their cagemom cohorts in both the water task and in skilled reaching. Condomom animals showed an increase in cortical thickness at anterior planes and thalamic area at both anterior and posterior regions. Golgi analyses revealed an increase in spine density. These results suggest that prenatal enrichment alters brain organization in manner that is prophylactic for perinatal brain injury. This result could have significant implications for the prenatal management of infants expected to be at risk for difficult birth.